Transient Characteristics and Operation Regulation of Grid‐Connected Variable Speed Pumped Storage‐Wind‐Solar Hybrid Power System - Yanhao Li; Fanchao Song; Wencheng Guo (Energy Science & Engineering)
ABSTRACT This article investigates the transient characteristics and operation regulation of grid‐connected variable speed pumped storage (VSPS)‐wind‐solar hybrid power system (HPS). Firstly, the model of grid‐connected VSPS‐wind‐solar HPS is established. Secondly, based on a calculating example, the transient characteristics of grid‐connected VSPS‐wind‐solar HPS are analyzed by using numerical simulation. Then, the effects of grid parameters and capacity ratios on transient characteristics of the grid‐connected VSPS‐wind‐solar HPS are revealed. Finally, the regulation of governor and frequency converter for the grid‐connected VSPS‐wind‐solar HPS is illuminated. The results indicate that the influence of wind speed disturbance and light intensity disturbance on the whole grid‐connected VSPS‐wind‐solar HPS can be effectively reduced by using the pitch angle controller and VSPS unit, and the overshoot of power grid frequency does not exceed 0.1%, and the adjustment time does not exceed 4.36 s. Compared to the isolated VSPS power station, the regulation quality of the transient characteristics of grid‐connected VSPS power station is worse. The coupling effect between the wind power station and power grid is weak. The increase of the capacity ratios of VSPS power station and wind power station has both advantages and disadvantages for the transient process of rotational speed of pump‐turbine. The increase of the capacity ratio of solar power station is disadvantageous for the transient process of rotational speed of pump‐turbine. The regulation effect of the control link PI‐1 plays a dominant role in the frequency converter. The effect of the parameters for the control links of frequency converter on the regulation quality of grid‐connected VSPS‐wind‐solar HPS is weaker than that of governor.